1993
DOI: 10.1111/j.1399-3054.1993.tb01361.x
|View full text |Cite
|
Sign up to set email alerts
|

De novo shoot morphogenesis and plant growth of mustard (Brassica juncea) in vitro in relation to ethylene

Abstract: Role of ethylene in de novo shoot morphogenesis from explants and plant growth of mustard (Brassica juncea cv. India Mustard) in vitro was investigated, by culturing explants or plants in the presence of the ethylene inhibitors aminoethoxyvinylglycine (AVG) and AgNO3. The presence of 20 μM AgNO3 or 5 μM AVG in culture medium containing 5 μM naphthaleneacetic acid and 10 μM benzyladenine were equally effective in promoting shoot regeneration from leaf disc and petiole explants. However, AgNO3 greatly enhanced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
53
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 41 publications
10
53
0
1
Order By: Relevance
“…Regarding leaf inhibition, a (Carvalho and Peres, 2005). Similarly, an inhibitory effect of ethylene on root growth has also been observed in other species (Pua and Chi, 1993;Rajala et al, 2002), including C. fimbriatum (Kerbauy and Colli, 1997). Despite the fact that ethylene led to a substantial reduction in growth of dark-grown shoots, it had practically no effect on either shoot size or dry mass of illuminated plants (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…Regarding leaf inhibition, a (Carvalho and Peres, 2005). Similarly, an inhibitory effect of ethylene on root growth has also been observed in other species (Pua and Chi, 1993;Rajala et al, 2002), including C. fimbriatum (Kerbauy and Colli, 1997). Despite the fact that ethylene led to a substantial reduction in growth of dark-grown shoots, it had practically no effect on either shoot size or dry mass of illuminated plants (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…1) using a range of explants. In our experiments, all the factors evaluated showed that cotyledon (Yang et al 2004), hypocotyls (Pua and Chi 1993), root sections (Bhalla and Smith 1998), and leaf segments (Guo et al 2005) were the most responsive explants for in vitro regeneration of Brassica species. In our study, cotyledons, hypocotyls, root and leaf segments were used as explants to determine the suitable explant type for regeneration of B. juncea L. All explants showed the development of shoots except root.…”
Section: Discussionmentioning
confidence: 95%
“…oleifera (Burnett et al 1994), Brassica campestris ssp. pekinensis (Chi et al 1991;Zhang et al 1998), hypocotyls of Brassica juncea (Pua and Chi 1993) and Raphanus sativus (Pua et al 1996), peduncle and leaf segments of Brassica napus (Eapen and George 1997;Akasaka-Kennedy et al 2005). AgNO 3 is a potent inhibitor of ethylene action, and ethylene is considered to suppress shoot morphogenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivation conditions, associated with the fact that passion fruit produces ethylene at high rates (Ludford, 1995), indicates that the possibility of ethylene accumulation in tissue culture flasks needs to be taken into account. Culture media supplementation with inhibitors blocking ethylene production or action, enhance morphogenesis in several plant species (Pua & Chi, 1993;Pestana et al, 1999;Mohiuddin et al, 1997). Faria & Segura (1997b) demonstrated that the addition of silver thiosulfate (STS) to culture media significantly increased the differentiation and development of adventitious shoots in passion fruit.…”
Section: Introductionmentioning
confidence: 99%